PENGARUH SERVICE QUALITY TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING - Citra Suci Mantauv (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2015)
The aim of this study is to find out how the Service Quality affecting Customer Loyalty and find out also whether the Customer Satisfaction acts as an intervening variable. From the results of this study, the variable Service Quality (X) significantly affects on customer loyalty (Y) where the regression coefficient is 0.308 with a significant level 0.000. However, the value of the regression coefficient variable Service Quality (X) increases from 0.308 into 0.589. The variable of Customer Satisfaction (I) as an intervening variable significantly affect on customer loyalty (Y) with regression coefficient 0.261 and significance level is 0.000. The amount of influence on Customer Loyalty Service Quality (Y) was 0.556 (R 2 = 55.6). In other words, The increase of the influence of the variables on Customer Loyalty Service Quality (Y) in the presence of intervening variables (Customer Satisfaction) amounted to 16.5% or from 55.6% to 7:21%. So, it can be interpreted that the variable of Customer Satisfaction (I) mediates partially (partial mediation) the relationship between the variables of Service Quality (X) to Customer Loyalty (Y). Keywords: Service Quality, Customer Loyalty, Customer Satisfaction